Pendekatan Strategis Pembinaan Akhlak Peserta Didik di SMK NU Kedungtuban Melalui Kelas Takhassus - Siti Nuraini; Abdul Mufid; Moh Imam Al Ghofiqi (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study focuses on the moral development strategy carried out by SMK NU Kedungtuban through the takhassus class. This study is intended to answer problems in moral development. This type of research is descriptive qualitative research with data collection of observation, interviews, and documentation. These results indicate that the strategy for developing students' morals through the takhassus class is, exemplary behavior, direction (providing guidance), encouragement, zakiyah and heart. While the strategy used in moral development at SMK NU Kedungtuban through the takhassus class includes making plans, organizing, directing and supervising to carry out activities related to moral development. Forms of habits carried out such as congregational prayer, joint tadarus and book studies are carried out routinely in the Takhassus class of SMK NU Kedungtuban. The inhibiting factors for the strategy of developing students' morals at SMK NU Kedungtuban through the takhassus class include the negative influence of social interactions from outside the school, limited study time, and the presence of students who are less disciplined such as often borrowing cell phones outside the takhassus class secretly. Meanwhile, the supporting factors for the strategy of developing students' morals at SMK NU Kedungtuban through the Takhassus class are full support from the foundation, teachers, parents, and a religious environment.